Product Innovation Analysis at Nyai Cipelah Chips MSME - Sumiati, Ai; Nurmayanti, Ade Rima; Anwar, Muhammad Kaisar; Putri, Liza Aulia; Komala, Rini Noerfiany (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2026)
Nyai Cipelah Chips is a local small business that demonstrates how basic ingenuity and innovation can fuel growth, even with minimum funding. Founded in 2023 and called after the owner's nickname,